2021
DOI: 10.1055/a-1608-0607
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular ATP Signaling Contributes to FAM3A-Induced PDX1 Upregulation in Pancreatic Beta Cells

Abstract: FAM3A is a recently identified mitochondrial protein that stimulates pancreatic-duodenal homeobox 1 (PDX1) and insulin expressions by promoting ATP release in islet β cells. In this study, the role of intracellular ATP in FAM3A-induced PDX1 expression in pancreatic β cells was further examined. Acute FAM3A inhibition using siRNA transfection in mouse pancreatic islets significantly reduced PDX1 expression, impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Interestingly, despite the discrepancy presented in previous reports in terms of the cellular vesicle transport and localization of FAM3A, almost all studies support the role of FAM3A as an impetus for oxidative respiration and intracellular ATP synthesis 7 – 9 , 13 , 23 , 38 . Correspondingly, the rates of O 2 consumption, oxidative respiration, and glycolysis were closely related to the smooth muscle contractile capacity and VSMC differentiation state 39 41 .…”
Section: Discussionmentioning
confidence: 60%
“…Interestingly, despite the discrepancy presented in previous reports in terms of the cellular vesicle transport and localization of FAM3A, almost all studies support the role of FAM3A as an impetus for oxidative respiration and intracellular ATP synthesis 7 – 9 , 13 , 23 , 38 . Correspondingly, the rates of O 2 consumption, oxidative respiration, and glycolysis were closely related to the smooth muscle contractile capacity and VSMC differentiation state 39 41 .…”
Section: Discussionmentioning
confidence: 60%
“…Mice with specific deletion of FAM3A in pancreatic β cells exhibit markedly impaired insulin secretion and glucose intolerance. In vitro , FAM3A overexpression enhances whereas FAM3A deficiency blunts ATP production and secretion, and GSIS in primary islets and β cell lines ( Yang et al, 2020 ; Yan et al, 2021 ). Mechanistically, FAM3A-promoted ATP release activates both P2X and P2Y receptors to increase cellular Ca 2+ , which stimulates the translocation of calmodulin (CaM) from cytoplasm into nucleus and directly interacts with forkhead box protein A2 (FOXA2) to augment its activation effect on the PDX-1 gene expression ( Yang et al, 2020 ).…”
Section: Atp Regulates Islet β Cell Functionsmentioning
confidence: 99%
“…Upregulation of PDX-1 finally induces insulin gene expression and insulin secretion ( Yang et al, 2020 ). Beyond extracellular ATP, intracellular ATP also contributed to FAM3A-induced PDX-1 upregulation and pancreatic β cell proliferation ( Yan et al, 2021 ). Moreover, Weitz et al (2018) also reported that ATP is a potent activator for islet macrophages, and mouse islet macrophages utilize locally released ATP to regulate islet β cell activity.…”
Section: Atp Regulates Islet β Cell Functionsmentioning
confidence: 99%
“…Previous studies have shown that FAM3 has important functions in diabetes, Alzheimer disease and cancer [15][16][17][18] . In particular, FAM3A is highly expressed in almost all tissues, which overexpression can elevate intracellular and extracellular ATP contents and facilitate PDX1 expression and insulin secretion 13,19 . FAM3B is originally found in pancreas and involved in glucose metabolism and lipogenesis 13,20 .…”
Section: Fam3 Family Genes Are Associated With Prognostic Value Of Hu...mentioning
confidence: 99%